An overview of atmospheric water harvesting methods, the inevitable path of the future in water supply. Issue 15 (5th April 2023) - Ahrestani, Zahra; Sadeghzadeh, Sadegh; Motejadded Emrooz, Hosein Banna
Abstract : Although science has made great strides in recent years, access to fresh water remains a major challenge for humanity due to water shortage for two-thirds of the world's population. Abstract : Although science has made great strides in recent years, access to fresh water remains a major challenge for humanity due to water shortage for two-thirds of the world's population. Limited access to fresh water becomes more difficult due to the lack of natural resources of water. Many of these resources are also contaminated by human activities. Many attempts have been made to harvest water from the atmosphere, and condensation systems have received much attention. One of the challenges in generation systems is the high consumption energy of the cooling feed, despite the generation of large amounts of water from the atmosphere. As other airborne contaminants condense with water vapor, the water after harvesting needs to be treated, which adds to construction and maintenance costs. Also, the need for high relative humidity in condensation systems has led scientists to find ways of atmospheric water harvesting at low relative humidity and use renewable energy sources. Sorption systems can absorb atmospheric water without the need for an energy supply and spontaneously. Desiccants such as silica gel and zeolite, due to their high affinity for water, can absorb water vapor in the air through physical or physicochemical bonding, but all of these have slow adsorption kinetics. Therefore, it takes a long time for the water harvesting cycle or they are not able to absorb water at low relative humidity, and others need a lot of energy for the water desorption phase. Metal–Organic Frameworks (MOF) are porous materials that, due to their special structure, are considered the most promising material for atmospheric water harvesting at low relative humidity. MOF-303 has been identified as the most efficient material to date and can harvest 0.7 liters of water per kilogram of MOF-303 at 10% RH and 27 °C. MOFs can harvest atmospheric water even in desert areas using only solar energy, and the water produced is drinkable and does not need to be treated. In this review, systems and methods of atmospheric water harvesting will be studied and compared and then the mechanism of adsorption and desorption in sorption systems will be discussed in detail.